Web-Based Gamification Loaded E-Learning Information System For Junior High Schools - Muhammad Reza Pahlevi; Ika Ratna Indra Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
Currently teaching and learning activities are carried out using E-learning facilities, E-learning is a means of teaching and learning activities from school to college. E-learning itself is now one of the standard learning methods in several schools and gamification is needed to support e-learning so that users are interested in its use. Gamification itself implements in-game features into a non-game context such as points, badges, and leaderboard. The method used in this research is the waterfall method which this method plans a system from upstream to downstream. In terms of appearance, this website looks attractive in for its users. This system is easy to use, so it is easier for students to do learning even though they are at home. The result of this research is that students can learn anywhere using available devices.